A Case Study of The Level of Public Awareness Regarding Household Waste Segregation in Urban Areas Was Conducted in Tonja Subdistrict, Denpasar City - Primadani, Ni Made Dwi; Dewi, Nyoman Diah Utari; Widnyani, Ida Ayu Putu Sri (Daengku: Journal of Humanities and Social Sciences Innovation, 2025)
Public awareness regarding the sorting of household waste is a critical component of sustainable environmental management initiatives. The objective of this study is to utilize a logistic regression analysis to examine the factors that influence the level of public awareness in sorting household waste. The independent variables that were the focus of the study included age, gender, education level, and employment status. The findings of the analysis indicate that gender, education level, and employment status exert a substantial influence on awareness of sorting waste (p-value <0.05). The probability that a woman will sort waste is 5.5 times greater than that of a man. As demonstrated in Figure 1, respondents with high school and college education levels exhibited a 11.3- and 13.9-fold increased likelihood of sorting waste, respectively, compared to respondents with junior high school education. The presence of both student status and employment was found to have a substantial impact on the probability of waste segregation, with odds ratios of 62.44 and 34.08, respectively. In contrast, the age variable did not demonstrate a statistically significant effect; however, a tendency was observed indicating that the productive age group exhibits a greater degree of awareness regarding waste sorting in comparison to the elderly. The Hosmer and Lemeshow test demonstrated that the logistic regression model employed was appropriate (p-value = 0.072). This finding emphasizes the importance of educational, occupational, and gender-based approaches in developing strategies to enhance public awareness regarding household waste segregation.